Effects of mastery and material value on life satisfaction among adults in the Klang Valley, Malaysia - Chandrasegaran, Anisha Joanne (2018)
To have a more profound comprehension of the relationship between materialism and life satisfaction, some consumer researchers have suggested the need to inspect probable effects of mediating, moderating, and third variables. The first objective of the current study is to determine the relationship between age, material value and life satisfaction among the young adults, midlife adults and older adults using a sample in the Klang Valley, Malaysia. Also another aim of the study was to examine the mediating impact of mastery between age and material value. The last objective of the study was to examine the moderating impact of mastery between material value and life satisfaction. This study is a cross-sectional correlational study in which data was collected during a brief period of time. A total of 593 adults (267 males, 326 females) in the Klang Valley, Malaysia were drawn to participate in this study using convenience sampling. The quantitative data were gathered using self-report questionnaires including Satisfaction with Life Scale (SWLS), Material Value Scale (MVS), Pearlin & Schooler Mastery Scale and a demographic information form. To be able to determine the mediating and moderating impact of mastery, Structural Equation Modelling (AMOS) was employed. The results showed that there was a relationship between these three variables, aligned with the first objective. It also revealed that material value negatively affected life satisfaction. 11% of the variance of life satisfaction was explained by materialistic values, which also attained statistical significance. Also, the results revealed that age is a contributing factor to an individual’s materialistic values although it only explained 12% of the variance, it was significant. This comes to show that materialistic values are harmful to life satisfaction.Besides, the results suggest that the relationship between age and materialism is partially mediated by mastery. Before the inclusion of mastery, age and materialism yielded, (β = -.35). Upon the inclusion of the mediator which was mastery the standardized regression coefficient reduced to (β = -.21). The result of bootstrapping is consistent with the mediation tests results gathered. In addition, the findings indicated that mastery moderated the relationship between material value and life satisfaction indicating that those possessing higher mastery have a reduced negative relationship between material value and life satisfaction. The standardized coefficient of the moderation effect was (β = .22) highlighting a moderate support for the relationship. Mastery is a crucial resource that protects one against the deleterious effects psychological stressors. Therefore, prevention and intervention programs should focus on people at risk of low or decreasing levels mastery, prioritizing the younger adults as the results of this study shows that this group possesses the lowest levels of mastery. Also, the findings of this study contributes to the scholarly world as prior studies have not studied the mediating and the moderating impact of mastery between the relationship of age, material value and life satisfaction respectively.